2020
DOI: 10.1021/acssuschemeng.0c02840
|View full text |Cite
|
Sign up to set email alerts
|

Fully Biobased Superpolymers of 2,5-Furandicarboxylic Acid with Different Functional Properties: From Rigid to Flexible, High Performant Packaging Materials

Abstract: In the present paper, four fully biobased homopolyesters of 2,5-furandicarboxylic acid (2,5-FDCA) with a high molecular weight have been successfully synthesized by two-stage melt polycondensation, starting from the dimethyl ester of 2,5-FDCA and glycols of different lengths (the number of methylene groups ranged from 3 to 6). The synthesized polyesters have been first subjected to an accurate molecular characterization by NMR and gel-permeation chromatography. Afterward, the samples have been successfully pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
173
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 104 publications
(199 citation statements)
references
References 62 publications
25
173
1
Order By: Relevance
“…The four polyesters were successfully processed into films by compression molding, and such films were subjected to thermal, diffractometric, mechanical, and gas permeability characterization. The results indicated that glycol subunit length determined the final polymer properties, finding an odd-even trend [31,32]. In detail, the polymers with an odd number of carbon atoms in the glycol subunit showed a lower tendency to crystallize with consequent formation of a less perfect crystalline phase, i.e., they were characterized by a lower melting temperature than the polymers obtained from glycol with an even number of carbon atoms, and they exhibited superior gas barrier performances.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…The four polyesters were successfully processed into films by compression molding, and such films were subjected to thermal, diffractometric, mechanical, and gas permeability characterization. The results indicated that glycol subunit length determined the final polymer properties, finding an odd-even trend [31,32]. In detail, the polymers with an odd number of carbon atoms in the glycol subunit showed a lower tendency to crystallize with consequent formation of a less perfect crystalline phase, i.e., they were characterized by a lower melting temperature than the polymers obtained from glycol with an even number of carbon atoms, and they exhibited superior gas barrier performances.…”
Section: Introductionmentioning
confidence: 93%
“…Mn (kg/mol) PDI Tg (K) Tm (K) PTF [24] 30 2.3 325 442 PBF [28,33] 36.1 * -308 437 PPeF [26] 29.6 2.4 286 -PHF [32] 28.9…”
Section: Samplementioning
confidence: 99%
See 3 more Smart Citations